CONCEPT DESIGN, VIRTUAL PROTOTYPING AND ERGONOMIC ANALYSIS OF AN INNOVATIVE SKIDDING WINCH USING A DES-TRIZ APPROACH - Di Gironimo, Giuseppe; Balsamo, Alessio; Esposito, Gianpiero; Melemez, Kenan; Lanzotti, Antonio (Amer Soc Mechanical Engineers, 2016)
The main objective of this work was to design an innovative skidding winch aimed to improve timber harvesting productivity, operators' safety, and reduce environmental damage in contexts in which mechanized harvesting is limited. The study area is the north-western Black Sea region of Turkey. In the proposed methodology, the harvesting process was simulated with Discrete Event Simulation (DES) software in order to identify bottlenecks. An alternative process was compared with the original one within the DES software itself in order to validate further steps oriented to generate new innovative product concepts. The development of the product was focused towards customer satisfaction, collecting customer requirements and identifying quality characteristics with a Quality Function Deployment approach. Contradictions identified in the design phase were solved using the TRIZ contradiction toolkit, generating different product concepts. Inventive solutions provided by TRIZ were designed within parametric CAD software. The concepts were compared in virtual environment with focus on ergonomics, selecting an optimal solution. The results show that with the concept adopted is possible to achieve a substantial increase in productivity, from 121% to 133%, in terms of kilograms of logs per hour deposited on the landing. Moreover, the final concept allows for ergonomic loading operations and reduces environmental damage to soil and vegetation.
ASME International Design Engineering Technical Conferences and Computers and Information in Engineering Conference -- AUG 02-05, 2015 -- Boston, MA
Keywords: Simulation; Reality